The contingencies of platform power and risk management in the gig economy - Niels van Doorn (Internet Policy Review, 2024)
What do we miss about the daily operations of platform power, and about power dynamics in the gig economy more broadly, when focusing on algorithmic management as the primary source of subordination and precarity in the workplace? Drawing on a five-year research project investigating platform-based food delivery and domestic cleaning in Amsterdam, Berlin, and New York City, this paper advances the argument that in order to understand the situated and contingent nature of platform power in the gig economy we should examine how gig workers manage risk. While a handful of studies have explicitly addressed this topic, we still know little about how socioeconomic stratification within gig workforces mediates workers' vulnerability to various kinds of risk, as well as their susceptibility to platform power. In response, the paper develops a "platform-adjacent" approach that situates gig work within people's larger work and life trajectories. It demonstrates how gig platforms can become both a resource for risk management and a new source of risk, depending on the complex interaction between a platform's labour management strategies on the one hand and the mix of support structures and dependencies in a worker's life on the other. Ultimately, the paper offers a more nuanced and comprehensive understanding of how gig platforms become integrated into people's everyday life and how platform power is articulated and negotiated over time.
Keywords: 300; Platform power; Gig economy; Risk; Platform-adjacent approach; Everyday life